(3GdfTQ aj GdbQGAGJ GdYTQs - (3eMeO Hf eMeO Hf eMeO Hf Ydj Hf jhSa, CHh GdNjQ, TeS GdOjf, GdYeQj GdOeTbqj Ke GdTjQGRj GdTGaYqj, GdTgjQ HGHf GdLRQj , J (B833 (3g` s ((3SYO Gddg Hf jYbhH GdNUchi s)
(3ChdgG (B:s
(3HGH MQa BNQ bQHJ eNGQLgG hJfMUQ ai SHYI YTQ MQakG s
(3BNQgG (B:s
(3aCQcGfg MVhQ GdbdH hGdQbI hGdESJcGfI hGdNThY , hJYdb GdbdH HGddg , hbWYI ef GdCSHGH , hCLfLI GdUOb hehGbjJg GdCSMGQ , hCSHGH GdUdGI Ydi GdfHi Udi Gddg Ydjg hSde Gddge Ud Ydi SjOfG eMeO hYdi Bd eMeO s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B275 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B292 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B188s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1952s
Keywords: (3GdbQGAGJ hGdJLhjOs